2011
DOI: 10.1063/1.3661982
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of interaction between passivated gold nanoparticles in supercritical CO2

Abstract: Molecular dynamics simulations have been performed to study the potential of mean force (PMF) between passivated gold nanoparticles (NPs) in supercritical CO(2) (scCO(2)). The nanoparticle model consists of a 140 atom gold nanocore and a surface self-assembled monolayer, in which two kinds of fluorinated alkanethiols were considered. The molecular origin of the thermodynamics interaction and the solvation effect has been comprehensively studied. The simulation results demonstrate that increasing the solvent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Theoretical investigations confirmed these data and revealed that increasing the length of the fluorous ligands could provide a strategy to devise more easily dispersible systems in Sc CO 2 [20]. Supercritical CO 2 also proved to be a good solvent for fluorous nanoparticles synthesis by using suitable organometallic precursors and hydrogen as reducing agent [21,22].…”
Section: "Perfluorinated" Gold Nanoparticlessupporting
confidence: 54%
“…Theoretical investigations confirmed these data and revealed that increasing the length of the fluorous ligands could provide a strategy to devise more easily dispersible systems in Sc CO 2 [20]. Supercritical CO 2 also proved to be a good solvent for fluorous nanoparticles synthesis by using suitable organometallic precursors and hydrogen as reducing agent [21,22].…”
Section: "Perfluorinated" Gold Nanoparticlessupporting
confidence: 54%
“…[73,74] The organization of the solvent around the solute and its influence on the solution structural and dynamic properties were investigated by means of MD for small solutes, [75][76][77][78][79][80][81][82][83][84] polymers [85,86] and proteins, [87] and passivated gold nanoparticles. [88] Some work based on Car-Parrinello MD was also performed. [89] Among the physicalp roperties of the solvated system,t he calculation of solubilities and the free energieso fs olvation is particularly important for the CO 2 medium, for which an enhancement of the solvation power represents ar eal challenge.…”
Section: Computational Studies Of Solvation In Pure Sccomentioning
confidence: 99%
“…[1, 2, 3, 4] Experimental studies performed on large NPs (100 nm) have shown that aspherical shapes require a smaller salt concentration to aggregate, due to the larger contact areas between them;[5, 6] while smaller sizes require larger salt concentrations to aggregate, due to the weaker van der Waals forces of attraction. [7, 8] Such small-sized NPs have presented novel challenges to traditional colloid science theories such as Derjaguin-Landau-Verwey-Overbeak (DLVO).…”
Section: Introductionmentioning
confidence: 99%